Hydrodynamic constraint loads estimation on connectors of column-pontoon type very large floating structure (CP-VLFS) under wave stimulation - Wu, Linjian; Jiang, Han; Ji, Xudong; Ju, Xueli; Xiang, Zhouyu; Gu, Mingjie (Frontiers in Marine Science, 2023)
Column-pontoon type very large floating structure (CP-VLFS) operated at the deep and sea faraway areas are generally exposed to the extremely complex wave conditions. The connectors of CP-VLFS are generally subjected to complicated hydrodynamic constraint loads when the modules of CP-VLFS are stimulated by the long-tern wave forces. The general method for analyzing the hydrodynamic performances for marine floating structures and their components is almost on the basis of potential flow/fluid theory (PFT), but its algorithm principle is relatively complex and would consume plenty of computing time. During the preliminary design and scheme comparison stages for CP-VLFSs, the hydrodynamic results for CP-VLFSs’ modules and their connectors required to be rapidly determined. Hence, a rapid and high-efficiency estimating method for time-domain hydrodynamic constraint loads of connectors on CP-VLFS considering the mathematical and mechanical model of rigid module and flexible connector (RMFC) is developed via this paper. During this estimation method, the Morison theory of floating body is employed to assess the hydrodynamic excitation forces by random and irregular wave (RIW) on CP-VLFS structures, and a series of concise formulas for estimating the hydrodynamic constraint loads of CP-VLFS connectors are derived based on the geometrical relationship of the CP-VLFS modules’ motion. For this paper’s explorations, a three-module CP-VLFS model is considered as a case, and the time-domain hydrodynamic constraint loads of CP-VLFS’s connectors are determined under the RIW stimulations with different wave angles. Hydrodynamic constraint loads of CP-VLFS connectors estimated by this paper agree well with the results of PFT and those of physical experiment, validation the methodologies developed by this paper. Some useful conclusions may provide significant technical supports for hydrodynamic characteristics of CP-VLFS modules and their connectors optimization.